2019
DOI: 10.1093/infdis/jiz180
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Kaposi’s Sarcoma–Associated Herpesvirus to Mortality in Hospitalized Human Immunodeficiency Virus–Infected Patients Being Investigated for Tuberculosis in South Africa

Abstract: Background Despite increasing numbers of human immunodeficiency virus (HIV)–infected South Africans receiving antiretroviral therapy (ART), tuberculosis (TB) remains the leading cause of mortality. Approximately 25% of patients treated for TB have microbiologically unconfirmed diagnoses. We assessed whether elevated Kaposi’s sarcoma–associated herpesvirus (KSHV) viral load (VL) contributes to mortality in hospitalized HIV-infected patients investigated for TB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
2
12
3
Order By: Relevance
“…KSHV DNA was detected in 20.6% (95% CI: 13.6-29.2%) with a median VL of 1.0 copies/10 6 cells (range 1.0-38,784 copies/10 6 cells). This percentage positive is significantly higher than that reported in our previous study (Blumenthal et al, 2019) [6.4% (95% CI: 4.7-8.4%); p < 0.0001]. Both EBV and KSHV DNA was detectable in 17.7% (95% CI: 11.1-26.2%) of the cohort.…”
Section: Clinical Characteristics Of the Study Participantscontrasting
confidence: 69%
See 2 more Smart Citations
“…KSHV DNA was detected in 20.6% (95% CI: 13.6-29.2%) with a median VL of 1.0 copies/10 6 cells (range 1.0-38,784 copies/10 6 cells). This percentage positive is significantly higher than that reported in our previous study (Blumenthal et al, 2019) [6.4% (95% CI: 4.7-8.4%); p < 0.0001]. Both EBV and KSHV DNA was detectable in 17.7% (95% CI: 11.1-26.2%) of the cohort.…”
Section: Clinical Characteristics Of the Study Participantscontrasting
confidence: 69%
“…KSHV infection is generally considered to be obtained in childhood in sub-Saharan Africa, with KSHV seroprevalence peaking before adulthood (Bourboulia et al, 1998) therefore it is unlikely these cases represent new infections. Indeed, while KSHV detection is greater in this cohort than what we have seen in pre-pandemic cohorts (Blumenthal et al, 2019), viral loads are significantly lower and it is plausible that the antibody levels in these cases fall below the detection limit of our assay. In severely ill patients, lytic KSHV infection can culminate in generalized inflammation and an IL-6 induced cytokine storm (described as KICS) (Uldrick et al, 2010;Polizzotto et al, 2012;Blumenthal et al, 2019).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It reaches 50% in Uganda [11,12], where the prevalence is already high in early childhood, with little increase thereafter, whereas the prevalence in South Africa and Zimbabwe in early adulthood is lower (<15%) and then increases with age [12]. In a recent study investigating patients with tuberculosis symptoms, the authors reported a seroprevalence of 30.7% in Cape Town South Africa [13].…”
Section: Geographical and Population Disparitiesmentioning
confidence: 99%
“…The distribution of KSHV varies globally. In some areas such as sub-Saharan Africa (SSA), KSHV seroprevalence can be as high as 80%, whereas in the US and Europe, the prevalence is 3%-20% [3,4]. The prevalence of KS increases significantly with HIV-1 infection, making it one of the leading cancers among people living with HIV/AIDS in SSA [5,6].…”
Section: Introductionmentioning
confidence: 99%